Leveraging Influencers to Reactivate Dormant Customers Effective Tactics and Metrics - Israwati, Israwati (Journal of Social Commerce, 2023)
The following is a look on how different influencer led methods could be applied to reactivate old customers and this include targeted messages, Special offers and discount, the use of stories and new products. The kind of research used in the studies involves the use of quantitative research where descriptive and inferential statistics are used to establish the impact of these approaches to consumer engagement and the cost of reactivation. The consequences monitor that consist of messages and extraordinary gives enhance reactivation efforts substantially while storytelling and new product displays also enhance positively though not to the same degree as the personalized messages and gives. This paper fills gaps in the literature relevant to the comparison of the techniques in question and, in specific reference to dormant clients, offers practical recommendations for the improvement of those approaches to influencer advertising. The learnings underlined the want for an array additional exam technique to seek successful reactivation and deliver useful advice on future advertising strategies.